Nanoscale Structure and Spectroscopic Probing of Aβ1-40 Fibril Bundle Formation - Psonka-Antonczyk, Katarzyna M.; Hammarström, Per; Johansson, Leif B. G.; Lindgren, Mikael; Stokke, Bjørn T.; Nilsson, K. Peter R.; Nyström, Sofie (Frontiers in Chemistry, 2016)
Amyloid plaques composed of fibrillar Amyloid-β (Aβ) is a hallmark of Alzheimer’s disease. However, Aβ fibrils are morphologically heterogeneous. Conformation sensitive luminescent conjugated oligothiophenes (LCOs) are versatile tools for monitoring such fibril polymorphism in vivo and in vitro. Biophysical methods applied on in vitro generated Aβ fibrils, stained with LCOs with different binding and fluorescence properties, can be used to characterize the Aβ fibrillation in depth, far beyond that possible for in vivo generated amyloid plaques. In this study, in vitro fibrillation of the Aβ1-40 peptide was monitored by time-lapse transmission electron microscopy, LCO fluorescence and atomic force microscopy. Differences in the LCO binding in combination with nanoscale imaging revealed that spectral variation correlated with fibrils transforming from solitary filaments (Ø 2.5 nm) into higher order bundled structures (Ø 5 nm). These detailed in vitro experiments can be used to derive data that reflects the heterogeneity of in vivo generated Aβ plaques observed by LCO fluorescence. Our work provides new structural basis for targeted drug design and molecular probe development for amyloid imaging.